2020
DOI: 10.3390/foods9030319
|View full text |Cite
|
Sign up to set email alerts
|

Radical Scavenging and Antimicrobial Properties of Polyphenol Rich Waste Wood Extracts

Abstract: The main focus of this study is to assess radical scavenging and antimicrobial activities of the 11 wood extracts: oak (Quercus petraea (Matt.) Liebl., Q. robur L., and Q. cerris L.), mulberry (Morus alba L.), myrobalan plum (Prunus cerasifera Ehrh.), black locust (Robinia pseudoacacia L.), and wild cherry (Prunus avium L.). High-performance thin-layer chromatography (HPTLC) provided initial phenolic screening and revealed different chemical patterns among investigated wood extracts. To identify individual com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 45 publications
2
16
0
1
Order By: Relevance
“…Namely, the consumption of bacteriologically unsafe drinking water is still one of the most significant causes of morbidity and mortality [19], especially in rural areas. Smailagić et al [20] investigated the antimicrobial activity of eleven wood extracts (oaks, mulberry, myrobalan plum, black locust, and wild cherry) against eight representative human and opportunistic pathogens. The lowest minimum inhibitory concentration (MIC) was observed against S. aureus for black locust, cherry, and mulberry wood extracts, and based on the conducted research, the usefulness of such wood waste for water disinfection is expected.…”
Section: Introductionmentioning
confidence: 99%
“…Namely, the consumption of bacteriologically unsafe drinking water is still one of the most significant causes of morbidity and mortality [19], especially in rural areas. Smailagić et al [20] investigated the antimicrobial activity of eleven wood extracts (oaks, mulberry, myrobalan plum, black locust, and wild cherry) against eight representative human and opportunistic pathogens. The lowest minimum inhibitory concentration (MIC) was observed against S. aureus for black locust, cherry, and mulberry wood extracts, and based on the conducted research, the usefulness of such wood waste for water disinfection is expected.…”
Section: Introductionmentioning
confidence: 99%
“…According to Alañón, Castro-Vázquez, Díaz-Maroto, Hermosín Gutiérrez, Gordon & Pérez -Coello (2011), the major contributors to the antioxidant capacity in wood samples are phenolic acids, such as gallic, protocatechuic, p-coumaric, and ellagic acid, and all the ellagitannins. Further, we reported that gallic acid, ferulic acid, p-coumaric acid, and caffeic acid, present in such samples, significantly contributed to the antioxidant capacity (Smailagić et al, 2020). All these compounds showed similar electrochemical behavior in the testing experimental conditions (Simić, Manojlović, Š egan & Todorović, 2007) with the corresponding oxidation peaks at similar potential.…”
Section: Initial Screening Of the Electrochemical Behavior And Potential Application Of CV And Dpv For Aging Monitoring And Wood Differenmentioning
confidence: 83%
“…So far, we have investigated the content of individual polyphenols by liquid chromatography with mass spectrometric detection, while spectrophotometric methods were used for conducting total phenolic content and antioxidant capacity (Smailagić et al, 2019). Also, individual compounds with radical scavenging activity were investigated using DPPH-HPTLC assay (Smailagić et al, 2020). Also, our research group investigated potential application of the electrochemical methods in the monitoring of the various biochemical or biological processes that affected the antioxidant capacity of the dominantly food samples.…”
Section: Introductionmentioning
confidence: 99%
“…Официнальным классическим лекарственным средством, обладающим вяжущими и противовоспалительными свойствами, является отвар коры дуба черешчатого [5][6][7]. За последнее время было проведено большое количество исследований, посвященных изучению антимикробных свойств коры дуба, а также препаратов на ее основе [8][9][10][11][12][13][14][15][16]. Кора дуба черешчатого входит в состав многих комплексных препаратов, например, «Стоматофит», «Тонзилгон Н», «Дентос» и др., а также используется для получения экстрактов, используемых в медицинских и косметологических целях 1 .…”
Section: Introductionunclassified